DAMPAK PROGRAM BINA IMAN ANAK KATOLIK TERHADAP PEMBENTUKAN IMAN DAN SIKAP ANAK DI PAROKI ST. CORNELIUS MADIUN - Saraswati, Fransiska Febrina Ayu; Wilhelmus, Ola Rongan (PERDIKKATI (Perkumpulan Pendidikan Keagamaan Katolik Indonesia), 2019)
This study explores various faith formation activities for Catholic children and their impact on faith development and attitude changes among them. The research focuses on highlighting the importance of faith formation programs in fostering spiritual growth and promoting positive behavioral changes in Catholic children. A qualitative approach was employed, with data collected through interviews. Purposive sampling was used to select participants, including three faith formation teachers, one parent, and one priest who were deeply involved in faith formation activities. The study presents four key findings: (1) faith formation teachers view their role as a calling and mission from God, (2) faith formation for Catholic children is a structured program designed to train and nurture faith, (3) the faith formation program in Region 3 St. Cornelius has been effectively implemented, with creative teachers actively engaging children in various activities, and (4) these activities have had a significant impact on the children’s faith development and attitudes, as evidenced by increased generosity, willingness to help others, forgiveness, and greater devotion in prayer.